Movie rolls, reel with Raton set, actors - Wildermuth, Todd (Raton Range Raton, NM, 1999)
Article on parts of a western movie being filmed in Raton.
Master List item # 30
File location is in the Raton File Cabinet
Keywords: Zeller, Ben; Miles, Marc; Jeeves, Sabe; McGuire, Marty; Fleming, Mark; Vandervalde, Ed; Raton Museum; Shuler Theater; Santa Fe Ranch; Zeller Ranch; Local History; Filming; Props; Actors; Raton, New Mexico; Denver Colorado; Colfax County; Santa Fe, New Mexico